Creation of mathematical model for estimating energy intensity of livestock wastes disinfection - Besarion C. Meskhi; Nikolay V. Limarenko; Victor P. Zharov; Boris G. Shapoval (Advanced Engineering Research)
Introduction. A perspective method of the livestock wastes disinfection is considered. The key point of the method is in complex physical and chemical impact of the variable magnetic field coupled with a chemical reagent. The device for implementing the proposed technique is an inductor. Electric energy intensity is selected as a parameter characterizing the energy efficiency of the of livestock wastes disinfection process. To increase the efficiency of investigating the livestock wastes disinfection process, it is proposed to use the mathematical experimental design theory. Materials and Methods. In the course of this research, the following techniques were used: instrument, direct and indirect methods of measurement, statistical processing technique, and mathematical experimental design theory. Research Results. The effect of technological factors on the energy efficiency of the livestock wastes disinfection process is experimentally investigated. On the basis of the data obtained, the strength effect ranking of the technology factors on the specific electrical energy capacity of the process is performed. A noncritical degree of impact of evaluating the pair-wise interaction coefficients is established. Their absence in the mathematical model suggests this. Discussion and Conclusions. A mathematical model of the livestock wastes disinfection process which allows evaluating the effect of the technology factors on the specific electrical energy intensity of the given process is developed.